2019
DOI: 10.1002/adhm.201801358
|View full text |Cite
|
Sign up to set email alerts
|

Safe Nanocomposite‐Mediated Efficient Delivery of MicroRNA Plasmids for Autosomal Dominant Polycystic Kidney Disease (ADPKD) Therapy

Abstract: There is currently no cure for gene mutation‐caused autosomal dominant polycystic kidney disease (ADPKD). Over half of patients with ADPKD eventually develop kidney failure, requiring dialysis or kidney transplantation. Current treatment modalities for ADPKD focus on reducing morbidity and mortality from renal and extrarenal complications of the disease. MicroRNA has been shown to be useful in treating ADPKD. This study combines anti‐miRNA plasmids and iron oxide/alginate nanoparticles for conjugation with ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…In addition, the results of the 2D fluorescence microscopy (Figure c–h) showed that by increasing the ratio of the nanocomposite, rGO/MWCNT/Fe 3 O 4 /ZnO, to CRISPR/Cas9, no significant EGFP was observed. However, by decreasing the mentioned ratio, the EGFP increased up to 11%, which is unprecedented among similar compounds and the highest recorded among nanocomposites (Figure b). In addition, in the absence of the ZnO compartment, the EGFP trends were contrariwise, which showed the effect of ZnO nanoparticles on the morphology and step sizes of the final nanocomposite as the active interaction sites. The reason for this observation could be due to the physical interaction between those nanocomposites and CRISPR/Cas9 as well as the AFM results, which indicates that by increasing the ratio of nanocomposite to CRISPR/Cas9, the size of the final nanoplex enhanced considerably as well as the ability of the nanocomposite to make a suitable physical interaction with the CRISPR/Cas9 was inhibited significantly. The inhibition of the physical interaction ability would be because of attaining a state of physical saturation that leads to J -aggregations as well as considerable agglomeration of the nanocomposites and the genetic material. ,, …”
Section: Resultsmentioning
confidence: 95%
“…In addition, the results of the 2D fluorescence microscopy (Figure c–h) showed that by increasing the ratio of the nanocomposite, rGO/MWCNT/Fe 3 O 4 /ZnO, to CRISPR/Cas9, no significant EGFP was observed. However, by decreasing the mentioned ratio, the EGFP increased up to 11%, which is unprecedented among similar compounds and the highest recorded among nanocomposites (Figure b). In addition, in the absence of the ZnO compartment, the EGFP trends were contrariwise, which showed the effect of ZnO nanoparticles on the morphology and step sizes of the final nanocomposite as the active interaction sites. The reason for this observation could be due to the physical interaction between those nanocomposites and CRISPR/Cas9 as well as the AFM results, which indicates that by increasing the ratio of nanocomposite to CRISPR/Cas9, the size of the final nanoplex enhanced considerably as well as the ability of the nanocomposite to make a suitable physical interaction with the CRISPR/Cas9 was inhibited significantly. The inhibition of the physical interaction ability would be because of attaining a state of physical saturation that leads to J -aggregations as well as considerable agglomeration of the nanocomposites and the genetic material. ,, …”
Section: Resultsmentioning
confidence: 95%
“…The Pkd1 L3/L3 (2L3) cell line was established by SV40 virus transduction of primary renal epithelial cells from 2L3 mice, an ADPKD mouse model, to induce an immortalized cell line [17,18]. Primary renal cells were infected in their second passage by using a Lenti-SV40 virus immortalization kit (Capital Biosciences Inc., Gaithersburg, MD, USA).…”
Section: Cell Linesmentioning
confidence: 99%
“…After reaching confluence, the cells were subcultured into a 10-cm dish with culture medium and were considered passage one (P1) cells. SV40transformed clones were selected, isolated by using cloning rings [17,18]. The M-1 cell line (Pkd1 +/+ ) purchased from BCRC (Hsinchu, Taiwan) was used as the wild type cell line.…”
Section: Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study and this study all showed that alg-MNPs are mainly excreted through the kidneys. 20 This indicated that alg-MNPs did not accumulate in the organs causing Figure 6 Ab-Vit.D-MNPs can ameliorate the side effects of vitamin D3 therapy in a peritoneal dialysis (PD) mouse model. (A) In the vitamin D3 group, serum calcium levels were significantly higher than those in the other groups; however, there was no hypercalcemia in the Ab-Vit.D-MNP group.…”
mentioning
confidence: 95%